Health risk perception of Karoo residents related to fracking, South Africa - Willems, Mieke (Department of Public Health and Family Medicine, 2015)
Shale gas exploration by means of Hydraulic Fracturing (fracking) has been on the South African (SA) energy agenda since 2010 as a potential alternative energy source to coalmining. Internationally, the desirability of fracking is debated due to increasing evidence of the environmental and health risks fracking poses. However, experts favouring fracking propose this technology as a greener alternative to conventional energy sources such as coal. Limited scientific evidence is available internationally related to knowledge and risk perceptions of fracking and evidence is limited to studies conducted in the United States (US). South African risk perception studies relates to mining, farming, travelling in SA as a foreigner and sexual behaviour. The president of SA called fracking a 'Game-Changer' using industry jargon in the 2014 presidential address. However, SA has failed to produce exploration regulations to date despite oil and gas companies pushing their agendas. Public participation in the process thus far has been limited. This cross sectional study explored the knowledge, health risk perceptions and information sources related to fracking amongst 102 Central Karoo residents through a household survey. Beaufort West municipality was selected as the study site as this is one of the closestareas to Cape Town demarcated for fracking exploration. This study found that 40% of Central Karoo residents do not know what fracking is or the potential risks and benefits thereof. Media is the main information source of 59% of participants. Only half of participants trust their information sources. Those with more trust in their information sources perceived fracking as posing a greater risk. In contrast those believing fracking to pose a low risk were more likely to trust the government and oil and gas companies. More than half of participants (53%) believe that fracking poses an extreme health risk and 78% thought fracking will harm their health. Most commonly listed causes why fracking will make Karoo residents sick includes water pollution (47.4%) and air pollution (19.6%). Higher education was found to have an inverse relationship with trust in the national government A limitation of this study was that farms could not be randomly selected, affecting the representativeness of the sample. There is a major lack of knowledge pertaining to fracking among those living in the Central Karoo which has important implications for managing the process of public participation in the approval of shale gas exploration.